EXERCISE 5.5 1. Simplify the following and leave the answers in expon \( \begin{array}{llll}\text { a) }\left(2^{6}\right)^{5} & \text { b) }\left(3^{4}\right)^{3} & \text { c) }\left(12^{2}\right)^{7} \\ \text { e) }\left(a^{3}\right)^{9} & \text { f) }\left(a^{2} b^{4}\right)^{5} & \text { g) }\left(a^{2} b^{3} c^{4}\right)^{6}\end{array} \) 2. Simplify as far as possible: \( \begin{array}{llll}\text { a) } 5^{2}\left(a^{4}\right)^{3} & \text { b) }\left(4^{2}\right)^{3} \div\left(2^{4}\right)^{3} & \text { c) } \\ \text { 3. Simplify: } & \text { b) } 5 a^{4}-\left(2 a^{2}\right)^{2} & \text { c) } \\ \begin{array}{llll}\text { a) }\left(2 a^{2} b^{3} c\right)^{3} & \text { b) } 3^{-2}+3 \frac{1}{3}-\left(\frac{3}{10}\right)^{-1} & \text { c) } \\ \text { 4. Simplify as far as possible: } \\ \text { a) } 3^{-1}-4^{-1} & & \end{array}\end{array} \begin{array}{l}\text { 5. Simplify }\left(5 a^{3}\right)^{2}-2\left(3 a^{3}\right)^{2}\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
Sure! Let’s simplify those expressions step by step. 1. a) \( (2^{6})^{5} = 2^{6 \cdot 5} = 2^{30} \) b) \( (3^{4})^{3} = 3^{4 \cdot 3} = 3^{12} \) c) \( (12^{2})^{7} = 12^{2 \cdot 7} = 12^{14} \) \( = (2^{2} \cdot 3^{2})^{14} = 2^{28} \cdot 3^{28} \) e) \( (a^{3})^{9} = a^{3 \cdot 9} = a^{27} \) f) \( (a^{2} b^{4})^{5} = a^{2 \cdot 5} b^{4 \cdot 5} = a^{10} b^{20} \) g) \( (a^{2} b^{3} c^{4})^{6} = a^{2 \cdot 6} b^{3 \cdot 6} c^{4 \cdot 6} = a^{12} b^{18} c^{24} \) 2. a) \( 5^{2}(a^{4})^{3} = 5^{2} a^{12} = 25 a^{12} \) b) \( \frac{(4^{2})^{3}}{(2^{4})^{3}} = \frac{4^{6}}{2^{12}} = \frac{(2^{2})^{6}}{2^{12}} = \frac{2^{12}}{2^{12}} = 1 \) c) 3. a) \( (2 a^{2} b^{3} c)^{3} = 2^{3} a^{6} b^{9} c^{3} = 8 a^{6} b^{9} c^{3} \) b) \[ 3^{-2} + 3 \frac{1}{3} - \left(\frac{3}{10}\right)^{-1} = \frac{1}{9} + 1 - \frac{10}{3} = \frac{1}{9} + \frac{9}{9} - \frac{30}{9} = -\frac{20}{9} \] c) 4. a) \[ 3^{-1} - 4^{-1} = \frac{1}{3} - \frac{1}{4} = \frac{4 - 3}{12} = \frac{1}{12} \] 5. \[ (5 a^{3})^{2} - 2(3 a^{3})^{2} = 25 a^{6} - 18 a^{6} = 7 a^{6} \] And that’s how you simplify these expressions! Happy calculating!